2019
DOI: 10.1111/dme.14099
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related behaviours in a remote Indigenous population with Type 2 diabetes: a Central Australian primary care survey in the Telehealth Eye and Associated Medical Services Network [TEAMSnet] project

Abstract: Aim There is a wealth of data concerning the health behaviours of Indigenous Australians, but the health behaviours of Indigenous Australians with diabetes are not systematically documented. At the clinical level, understanding a person's health behaviours can help identify and address barriers to diabetes care and promote good clinical outcomes. Methods We used a novel survey tool to systematically collect health behaviour data on Smoking, Nutrition, Alcohol consumption, Physical activity and Emotional well‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 24 publications
5
20
0
Order By: Relevance
“…This study of Indigenous Australians with diabetes demonstrated that although less than half the study group consumed alcohol, high‐risk or likely dependent alcohol use or binge drinking was common amongst drinkers. The proportion of participants consuming alcohol in the past year (43%) was similar to a recent Central Australian study of adults with diabetes attending a remote primary clinic in which 38% of participants consumed alcohol, with men consuming more alcohol than Indigenous women (Xu et al, 2019) unlike the present study in which the proportion of men and women who were drinkers was similar ( p = .179). Safe alcohol use should be a routine part of diabetes assessment and education.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study of Indigenous Australians with diabetes demonstrated that although less than half the study group consumed alcohol, high‐risk or likely dependent alcohol use or binge drinking was common amongst drinkers. The proportion of participants consuming alcohol in the past year (43%) was similar to a recent Central Australian study of adults with diabetes attending a remote primary clinic in which 38% of participants consumed alcohol, with men consuming more alcohol than Indigenous women (Xu et al, 2019) unlike the present study in which the proportion of men and women who were drinkers was similar ( p = .179). Safe alcohol use should be a routine part of diabetes assessment and education.…”
Section: Discussionsupporting
confidence: 85%
“…Despite this, based on the NHMRC Australian Dietary Guidelines, only 6% met the recommended adequate daily vegetable intake, 25% had adequate daily fruit intake, and 19% consumed the recommended fish intake of two or more servings daily (National Health & Medical Research Council, 2013). The observed low vegetable intake of participants is consistent with the low vegetable intake of the broader Australian population and for Indigenous Australians with diabetes in remote Australia (Xu et al, 2019), where food insecurity is likely to be more prevalent. As expected, fish intake was higher among study participants, surrounded by rivers and lakes, than their counterparts in remote Central Australia, surrounded by deserts and dry river beds.…”
Section: Discussionsupporting
confidence: 81%
“…Site differences in DR prevalence may also be due to differences in health behaviours of the communities. For example, in our TEAMSnet Central Australian cohort with a higher STDR prevalence, we reported suboptimal diet quality, physical activity and emotional well‐being, although smoking prevalence was lower than in the national indigenous population 21 . No comparable behavioural data are available for the Top End cohort, but it is plausible that the Top End coastal communities may have different health behaviours, for example better diet than desert communities.…”
Section: Discussionmentioning
confidence: 75%
“…[ 35 ] As an asymptomatic disease, patient attitude and health-related behaviors play significant roles in the success of these programs. [ 31 36 ] Education support is required for people to want to access treatment when they are asymptomatic. Communication between the referrer and the patient needs to be improved significantly.…”
Section: Review Of Barriers and Potential Remediesmentioning
confidence: 99%